2018
DOI: 10.1177/0040517518821899
|View full text |Cite
|
Sign up to set email alerts
|

Representations of fabric hand attributes in the cerebral cortices based on the Automated Anatomical Labeling atlas

Abstract: Fabric hand is most frequently used by consumers and researchers to evaluate the touch feeling of textiles. Academically, many methods have been developed to characterize it psychologically and physically, and the relationship between the hand attributes of fabrics and their physical properties are well understood. However, in physiological terms, the cognitive mechanism of the brain on different attributes of fabric hand is not clear. Previous studies have shown that the sensory or discrimination information … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 58 publications
(56 reference statements)
0
3
0
Order By: Relevance
“…One of the most recognized software toolkits, SPM12 (developed by members & collaborators of the Wellcome Centre for Human Neuroimaging, London, UK; http://www.fil.ion.ucl.ac.uk/spm), was adopted to process the anatomical and functional brain data of the participants acquired from the MRI scanner. The method and procedure of the data preprocessing are in accord with the previous study, 14 and statistical analysis was carried out using the general linear model 17 . Finally, after doing group analysis of one‐sample t test for all participants’ fMRI data, activation information in brain regions was acquired.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most recognized software toolkits, SPM12 (developed by members & collaborators of the Wellcome Centre for Human Neuroimaging, London, UK; http://www.fil.ion.ucl.ac.uk/spm), was adopted to process the anatomical and functional brain data of the participants acquired from the MRI scanner. The method and procedure of the data preprocessing are in accord with the previous study, 14 and statistical analysis was carried out using the general linear model 17 . Finally, after doing group analysis of one‐sample t test for all participants’ fMRI data, activation information in brain regions was acquired.…”
Section: Methodsmentioning
confidence: 99%
“…6,8 Although mechanical causes from the stimuli (fiber ends) and physiological principle of the cutaneous receptors (evoked activity of nociceptors) have been both well understood, the brain mechanism for perceiving fabric-evoked prickle is still unclear. Previously, using the technology of functional magnetic resonance imaging (fMRI), we analyzed the response signal of the brain on the tactile stimulation of fabric by finger touch, 14,15 showing that fMRI is a promising tool for studying the cognitive mechanism of the brain on the mechanical stimulation of fabric touch on the skin. Moreover, through comparing the brain activity evoked by fabric touch on human glabrous (palm) and hairy skin (forearm), 16 we found that there is more emotional information arising from fabric touch on the hairy skin (forearm), and brain activity in the insula cortex is an important information for the evaluation of fabric comfort.…”
mentioning
confidence: 99%
“…fMRI technology measures brain activity by detecting changes of blood flow associated with tactile perception with a high spatial resolution [18]. fMRI technology has been used to investigate the brain functional response to the cutaneous prickling of fiber [19] and the surface roughness of fabric [20], the primary brain regions related to the fabric hand [21], and the fabric comfort perception [22]. The previous studies have proved that fMRI is a remarkable tool to study the cognitive mechanism of the brain on the mechanical stimulation of fabric on human skin.…”
Section: Introductionmentioning
confidence: 99%